Historical Hero Mazan Bator (By oral stories written from T.S. Tyaginova) - B. M. Kovaeva (Nomadic Civilization: Historical Research)
The history of Kalmyks is rich in material. Certainly there were honorable people in the history of Kalmyks. Their names will not be forgotten. One of them is Mazan Bator. In 1672-1677, Mazan Bator was the leader of the army, which stood up along with the Russians and Circassians for the enemy, gave their life, and poured their red blood. Some documents about Mazan are stored in the Central State Archive of Ancient Acts (TsGADA) in Moscow. Nowadays, many things are known about Mazan. This name is also included in many legends and has been immortalized among the Kalmyks. In this article, 3 oral story told by by T. S. Tyaginova will be published. These 3 story were written in the spring of 2018 by B. M. Kovaeva who listened Tyaginova, recorded her words with a video camera, and by hand. Oral history is the collection and study of historical information about individuals, important events using audiotapes, videotapes, or transcriptions of interviews. The oral stories about brave warrior, who had a good mind and a good heart, published in this article, reveal the history of the Kalmyks. There are some words borrowed from the Russian language. Mazan’s heroic character deserves to be highlighted in public memory and opinion.